Evaluasi Kebijakan Program Rehabilitasi Sosial Gelandangan Dan Pengemis Di Panti Rehabilitasi Sosial Bina Karya - Lubis, Muhammad Aldi (CV The Journal Publishing, 2024)
The number of Penyandang Masalah Kesejateraan Sosial (PMKS), especially Homeless people and Beggars in West Java Province is increasing. The number of Penyandang Masalah Kesejateraan Sosial (PMKS), especially Homeless people and Beggars in West Java Province is increasing in resolving poverty problems in the homeless and beggar categories which have physical, mental and spiritual guidance programs, individual social guidance. Knowing the results of the policy evaluation of the homeless and beggar program and to find out the efforts made by the orphanage in evaluating program policies and factors hindering program policy evaluation. The method used in this research is qualitative and data collection techniques are carried out by direct observation in the field, in-depth interviews, and documentation. The results of the research show that the program implementation activities that are applied to homeless people and beggars are in the form of services and rehabilitation, including through various guidance activities, both in the form of spiritual, physical, social, mental and skills guidance and the program is considered ineffective because there are still clients after training returns to the streets The Orphanage evaluates in early 2020 to the new management and has applied direct work distribution to clients and also provides a rented house for the first year to be paid by the orphanage, it is hoped that after it is distributed to the work place.